2012
DOI: 10.1371/journal.pone.0042498
|View full text |Cite
|
Sign up to set email alerts
|

The Octadecaneuropeptide ODN Protects Astrocytes against Hydrogen Peroxide-Induced Apoptosis via a PKA/MAPK-Dependent Mechanism

Abstract: Astrocytes synthesize and release endozepines, a family of regulatory peptides, including the octadecaneuropeptide (ODN) an endogenous ligand of both central-type benzodiazepine (CBR) and metabotropic receptors. We have recently shown that ODN exerts a protective effect against hydrogen peroxide (H2O2)-induced oxidative stress in astrocytes. The purpose of the present study was to determine the type of receptor and the transduction pathways involved in the protective effect of ODN in cultured rat astrocytes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 65 publications
5
46
0
Order By: Relevance
“…ODN is a potent protective agent that prevents oxidative stress‐induced apoptosis and attenuates H 2 O 2 ‐evoked inhibition of SOD and catalase activities in astrocytes (Hamdi et al, 2011). It has been suggested that the anti‐apoptotic activity of ODN is mediated through a putative GPCR coupled to the adenylate cyclase/protein kinase A pathway (Hamdi et al, 2012). Downstream of protein kinase A, ODN induces ERK phosphorylation which, in turn, activates the expression of the anti‐apoptotic gene Bcl‐2 and blocks the stimulation by H 2 O 2 of the proapoptotic gene Bax.…”
Section: Potential Therapeutic Targets In Astrocytesmentioning
confidence: 99%
“…ODN is a potent protective agent that prevents oxidative stress‐induced apoptosis and attenuates H 2 O 2 ‐evoked inhibition of SOD and catalase activities in astrocytes (Hamdi et al, 2011). It has been suggested that the anti‐apoptotic activity of ODN is mediated through a putative GPCR coupled to the adenylate cyclase/protein kinase A pathway (Hamdi et al, 2012). Downstream of protein kinase A, ODN induces ERK phosphorylation which, in turn, activates the expression of the anti‐apoptotic gene Bcl‐2 and blocks the stimulation by H 2 O 2 of the proapoptotic gene Bax.…”
Section: Potential Therapeutic Targets In Astrocytesmentioning
confidence: 99%
“…Treatment with bucladesine significantly reduced cleaved caspase-3 activity as well as TUNEL-positive cells. Elevation of intracellular cAMP modulates the Bax/Bcl-2 balance in favor of an antiapoptotic activity leading to an inhibition of H 2 O 2 -induced caspase-3 via the intrinsic apoptotic mitochondrial pathway [10]. Our results revealed that cuprizone raised the ratio of Bax/Bcl-2 and bucladesine decreased this ratio.…”
Section: Discussionmentioning
confidence: 57%
“…Caspase-3 is well known as a downstream executioner caspase of caspase-dependent apoptotic cascades. Bucladesine could decrease the caspase-3 activity induced by H 2 O 2 in the cell culture [10]. As shown in Fig.…”
Section: The Effect Of Bucladesine On Apoptotic Markersmentioning
confidence: 70%
See 1 more Smart Citation
“…DBI and its processing products are collectively designated by the term endozepines [39]. ODN acts through two types of receptors, the central-type benzodiazepine receptors (CBR) associated with the GABA A receptor complex [6,18] and a metabotropic receptor positively coupled to either phospholipase C (PLC) [28] or adenylyl cyclase (AC) [24]. The primary structure of ODN has been strongly conserved during evolution [10,39], suggesting that this peptide plays important biological functions.…”
Section: Introductionmentioning
confidence: 99%